Dinamika Penerapan Hukum Adat Port Numbay: Analisis Tren Kontemporer di Kota Jayapura - Sara Ida Magdalena Awi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the dynamics of the application of Port Numbay customary law in the contemporary context of Jayapura City. The research method used is a qualitative approach with a case study. Data were collected through in-depth interviews with traditional leaders, indigenous communities, academics, and other stakeholders. Data analysis was conducted using content analysis and qualitative interpretation techniques. The results of the study indicate that the application of Port Numbay customary law has undergone significant changes along with the times, the influence of globalization, and the Papuan special autonomy policy. These changes include adaptation to the state legal system, shifts in traditional values, and the emergence of new challenges related to conflicts over customary rights and development. Nevertheless, Port Numbay customary law continues to play a significant role in maintaining cultural identity, resolving disputes, and maintaining social harmony within the community. The study's conclusions emphasize the importance of strengthening the role of customary law, harmonizing it with the state legal system, and active participation of the Port Numbay customary law community in decision-making processes related to the management of customary law. Research recommendations include the need to revitalize customary values, increase the capacity of customary institutions, and develop policies that support the sustainability of Port Numbay customary law.